2012
DOI: 10.1111/j.1600-0501.2012.02537.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of general dental practitioners towards implant dentistry in an environment with widespread provision of implant therapy

Abstract: In a community where provision of dental implants is widespread among its General Dental Practitioners (GDPs), their attitudes are not wholly in line with evidence-based knowledge. Variations in their attitudes existed with respect to dentist factors, training and experience issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 31 publications
1
20
1
Order By: Relevance
“…, Fardal & Grytten , Lang‐Hua et al. ), and might also be costly long term due to technical and biological complications (Jung et al. ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…, Fardal & Grytten , Lang‐Hua et al. ), and might also be costly long term due to technical and biological complications (Jung et al. ).…”
mentioning
confidence: 99%
“…Moreover, retaining teeth via supportive periodontal treatment (SPT) was shown affordable in several settings, with both initial and long-term costs generally being lower for retained teeth than for their replacement (Pretzl et al 2009, Fardal & Grytten 2013. Such replacement via implant-supported crowns (ISCs), however, is increasingly common, but generates high initial costs (Pretzl et al 2009, Fardal & Grytten 2013, Lang-Hua et al 2013, and might also be costly long term due to technical and biological complications (Jung et al 2012).…”
mentioning
confidence: 99%
“…; Lang‐Hua et al. ). In the current investigation, questions related to maintenance care and treatment of peri‐implant diseases were included and revealed that implant placement was more often conducted than treatment of the most frequent biological complications (33.5% implant placement vs. 29.7% treatment of peri‐implant disease).…”
Section: Discussionmentioning
confidence: 98%
“…Another study dealing with treatment planning revealed that dentists perceived implants to be superior to conventional prostheses for the replacement of a single missing posterior tooth and likewise, for the replacement of a single missing anterior tooth (Lang‐Hua et al. ). Through these findings, one can infer that patient's choice of dental care provider could influence the selection of therapeutic options.…”
mentioning
confidence: 99%
“…[8] Hence the choice between CRR and SRR is based on the patient based clinical findings and clinicians' preference. Since implant dentistry has revolutionized the modern dental practice and increased numbers of general dental practitioners (GDP's) are involved in the provision of implant-retained restorations, [22] it is hypothesized that the knowledge of GDP's and specialist (SP) regarding implant-retained restorations is comparable. Therefore, the aim of this study was to evaluate the knowledge and attitude of SP and GDP regarding factors effecting decision-making between CRR and SRR implant restorations.…”
Section: Introductionmentioning
confidence: 99%